2014
DOI: 10.2478/micsm-2014-0002
|View full text |Cite
|
Sign up to set email alerts
|

Genetically identical co-housed pigs as models for dietary studies of gut microbiomes

Abstract: The impact of diet on the microbial composition in the gastrointestinal tract (GIT) has been well documented. However, quantifying the role of the diet in shaping microbial composition in humans has been difficult due to the influence of host genetics and the environment. To test the influence of diets on the GIT microbiome independently of host genotype and environment, two genetically identical co-housed pigs were used in an A-B-A-B design across four 14-day periods using two distinct diets that differed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 66 publications
0
1
0
Order By: Relevance
“…This observation is consistent with that of Korecka et al [ 40 ] who showed using whole body AhRKO mice that the absence of AhR activity did not significantly influence the fecal or colonic microbiome composition, but only altered the small intestinal bacterial community. The stronger influence of diet on the fecal microbiome could be because of the altered supply of nutrients that drives a direct change in the fecal microbial composition [ 41 ]. On the other hand, AhR expression likely plays an indirect role in shaping the microbiome composition.…”
Section: Discussionmentioning
confidence: 99%
“…This observation is consistent with that of Korecka et al [ 40 ] who showed using whole body AhRKO mice that the absence of AhR activity did not significantly influence the fecal or colonic microbiome composition, but only altered the small intestinal bacterial community. The stronger influence of diet on the fecal microbiome could be because of the altered supply of nutrients that drives a direct change in the fecal microbial composition [ 41 ]. On the other hand, AhR expression likely plays an indirect role in shaping the microbiome composition.…”
Section: Discussionmentioning
confidence: 99%